Implementasi Algoritma Fisher Yates Shuffle pada Aplikasi Belajar Huruf Hijaiyah - Irfan Kurniawan; Siti Sauda (APTIKOM SUMSEL, 2021)
The form of coaching for early childhood is providing stimulation so that children have readiness to enter the next level of education. One of the basic educations provided by parents is religious education in the form of introduction to hijaiyah letters. Children interacting with smartphones more often than books, causing parents to have basic education such as reading and writing using books to be less attractive to children. From this problem, the writer wants to build a learning media application using smartphone media. This Hijaiyah Letter Learning application was created using the fisher yates shuffle algorithm, by randomizing the questions in this application. Based on the test results that the implementation of the Fisher Yates Shuffle algorithm for randomization of questions in the hijaiyah learning application is running well, there are no questions that appear repeatedly.